2023
DOI: 10.3390/f14071288
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Microbial Communities and Functions to Long-Term Tea (Camellia sinensis L.) Planting in a Subtropical Region

Abstract: Soil microbes are the key to revealing the mechanisms driving variation in soil biogeochemical processes. In recent decades, forests in Southeast China have been widely transformed into tea plantations due to the drivers of economic benefits. However, the changes in the soil microbial community and their potential function during the transition from a typical forest ecosystem to tea plantations remain poorly understood. This study investigated the soil microbial community in tea plantation soils with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Besides, the use of nitrogen-based fertilizers to increase yield in tea gardens could be responsible for the abundance of Proteobacteria in soil because they are actively involved in nitrogen conversions in soil. Likewise, a recent study conducted by Zheng et al (2023) through the direct extraction of soil DNA and high-throughput sequencing to investigate soil microbial communities structure in tea plantations in the Southeast region of China, reported the relative abundance of bacterial phyla corresponding to Proteobacteria (20.96-41.40%), Acidobacteria (9.41-28.42%), Firmicutes (6.39-16.03%), Bacteriodetes (6.05-13.80%), Chloroflexi (3.35-13.27%) and Actinobacteria (2.37-11.52%) being dominant phyla. Lynn et al (2017), through the direct extraction of soil microbial DNA and 16S rRNA sequencing also demonstrated that Actinobacteria, Chloroflexi, Acidobacteria, Proteobacteria, Firmicutes dominated the diverse bacterial communities in tea plantations found in Southern region of China.…”
Section: Bacterial Communities In Soils Of Tea Gardensmentioning
confidence: 89%
See 3 more Smart Citations
“…Besides, the use of nitrogen-based fertilizers to increase yield in tea gardens could be responsible for the abundance of Proteobacteria in soil because they are actively involved in nitrogen conversions in soil. Likewise, a recent study conducted by Zheng et al (2023) through the direct extraction of soil DNA and high-throughput sequencing to investigate soil microbial communities structure in tea plantations in the Southeast region of China, reported the relative abundance of bacterial phyla corresponding to Proteobacteria (20.96-41.40%), Acidobacteria (9.41-28.42%), Firmicutes (6.39-16.03%), Bacteriodetes (6.05-13.80%), Chloroflexi (3.35-13.27%) and Actinobacteria (2.37-11.52%) being dominant phyla. Lynn et al (2017), through the direct extraction of soil microbial DNA and 16S rRNA sequencing also demonstrated that Actinobacteria, Chloroflexi, Acidobacteria, Proteobacteria, Firmicutes dominated the diverse bacterial communities in tea plantations found in Southern region of China.…”
Section: Bacterial Communities In Soils Of Tea Gardensmentioning
confidence: 89%
“…Thus, these abilities may be linked to their ubiquity and potentials to protect plants against pathogens. Zheng et al (2023) investigated the response of soil microbial communities and functions to long-term tea (C. sinensis) planting in a subtropical region and reported the relative abundance of fungal community in tea gardens to be largely dominated by .13%), Mortierellomycota (1.8-10.1%), and Rozellomycota (0.12-7.41%). Similarly, Ma et al (2022) in a study conducted on soils of tea plantations revealed that fungal community predominantly consisted Earlier reports indicated that fungal communities in several tea gardens at the genus level are dominated primarily by Saitozyma (Ma et al, 2022;Wang et al, 2023).…”
Section: Fungal Communities In Tea Gardens Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…S4 ), soil pH, TN, and invertase were the main contributors to the microbial taxa and functions. Soil pH can affect soil nutrient solubility and availability to plants and the soil microbial community ( Naz et al, 2022 ; Zheng et al, 2023 ). As an essential nutrient, soil nitrogen is generally the limiting factor for plants in terrestrial ecosystems, resulting in strong competition between microorganisms and plants ( Geisseler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%